Conductive Fe3O4 Nanoparticles Accelerate Syntrophic Methane Production from Butyrate Oxidation in Two Different Lake Sediments - Zhang, Jianchao; Lu, Yahai (Frontiers in Microbiology, 2016)
Syntrophic methanogenesis is an essential link in the global carbon cycle and a key bioprocess for the disposal of organic waste and production of biogas. Recent studies suggest direct interspecies electron transfer (DIET) is involved in electron exchange in methanogenesis occurring in paddy soils, anaerobic digesters and specific co-cultures with Geobacter. In this study, we evaluate the possible involvement of DIET in the syntrophic oxidation of butyrate in the enrichments from two lake sediments (an urban lake and a natural lake). The results showed that the production of CH4 was significantly accelerated in the presence of conductive nanoscale Fe3O4 or carbon nanotubes (CNTs) in the sediment enrichments. Observations made with fluorescence in situ hybridization (FISH) and scanning electron microscope (SEM) indicated that microbial aggregates were formed in the enrichments. It appeared that the average cell-to-cell distance in aggregates in nanomaterial-amended enrichments was larger than that in aggregates in the non-amended control. These results suggested that DIET-mediated syntrophic methanogenesis could occur in the lake sediments in the presence of conductive materials. Microbial community analysis of the enrichments revealed that the genera of Syntrophomonas, Sulfurospirillum, Methanosarcina and Methanoregula were responsible for syntrophic oxidation of butyrate in lake sediment samples. The mechanism for the conductive-material-facilitated DIET in butyrate syntrophy deserves further investigation.